Removal of Large Urinary Stone Using Percutaneous Nephrolithotomy in a Patient with Crohn’s Disease - Young Joo Park; Dong Hoon Baek; Young Min Kwak; Yong Bo Park; Dong Chan Joo; Tae Kyung Ha; Da Mi Kim; Geun Am Song (Kosin Medical Journal, 2021)
Extraintestinal manifestation (EIM) of inflammatory bowel disease (IBD) is approximately 36%. Of genitourinary complications as an EIM of Crohn’s disease (CD), nephrolithiasis is the most common urinary complication in patients with CD. CD patients have been shown to have decreased urinary volume, pH, magnesium, and excretion of citrate, all of which are significant risk factors for nephrolithiasis. Genitourinary complications often occur in case of a severe longstanding disease and are associated with, the activity of bowel disease, especially in those who have undergone bowel surgery. As uncontrolled nephrolithiasis could impair renal function as well as adversely affect quality of life, proper monitoring, early detection, and prevention of the occurrence of urologic complications in CD is crucial. Few data are available about urolithiasis in patients with CD. Herein we report a case of a successful removal of a 2.7 cm calcium oxalate stone using percutaneous nephrolithotomy from a patient with long-standing CD with a previous surgery for small intestinal and colonic stricture.